Pendampingan Pemasaran Digital untuk Meningkatkan Jangkauan Pasar pada UMKM Songket Fikri Palembang - Weni Susanti; suharti; Herman Efrizal (Jurnal Ekonomi Mengabdi, 2026)
The development of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to utilize digital marketing in order to enhance their business competitiveness. However, Songket Fikri, a traditional songket weaving MSME in Palembang City, still faces challenges in utilizing digital media, resulting in suboptimal product marketing. This community service program aimed to improve the partner’s digital marketing capabilities through training and mentoring activities. The methods employed included observation, interviews, training, and mentoring related to social media optimization, promotional content creation, product photography, and the development of digital marketing strategies. The results indicated an improvement in the partner’s knowledge and skills in utilizing digital media for product promotion. The partner became more capable of managing social media effectively and creating more attractive marketing content. This program contributed positively to expanding market reach, enhancing business competitiveness, and supporting the preservation and promotion of Palembang songket through digital media. Abstrak Perkembangan teknologi informasi mendorong UMKM untuk memanfaatkan pemasaran digital guna meningkatkan daya saing usaha. Namun, Songket Fikri sebagai salah satu UMKM pengrajin songket di Kota Palembang masih menghadapi kendala dalam pemanfaatan media digital sehingga pemasaran produk belum optimal. Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kemampuan pemasaran digital mitra melalui pelatihan dan pendampingan. Metode yang digunakan meliputi observasi, wawancara, pelatihan, dan pendampingan terkait optimalisasi media sosial, pembuatan konten promosi, fotografi produk, serta penyusunan strategi pemasaran digital. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan dan keterampilan mitra dalam memanfaatkan media digital untuk promosi produk. Mitra mampu mengelola media sosial secara lebih efektif dan menghasilkan konten pemasaran yang lebih menarik. Kegiatan ini memberikan kontribusi positif dalam memperluas jangkauan pasar, meningkatkan daya saing usaha, serta mendukung pelestarian dan promosi songket Palembang melalui media digital.